The investigation of the properties of filaments fabricated from carbon biomass and LLDPE - Pramono, Agus Edy; Patrick, Yohannes; Zuhri, Aminudin; Setiyadi, Iman; Maksum, Ahmad; Indayaningsih, Nanik; Subyakto, Subyakto (Jurnal Polimesin, 2024)
This study aims to develop composites using electrically conductive carbon and polymer polyethylene (LLDPE) to enhance electrical conductivity. Investigations have been conducted on the fabrication of electrically conductive composites and the modulus of elasticity through heat compaction using mixtures of carbon-LLDPE powders. Heat compaction is performed at temperatures ranging from 120°C to 150°C, with varying composition ratios of carbon-LLDPE, including 50:50, 60:40, and 70:30 % wt. Higher proportions of carbon and compaction temperatures are correlated with increased electrical conductivity. For instance, the C7-3LLDPE composite, compacted at 150°C, demonstrates the highest electrical current flow of 0.0018 A, whereas the C5-5LLDPE composite, compacted at 135°C, exhibits the lowest current flow at 0.0000638 A. Regarding the modulus of elasticity, the composition ratio of C7-3LLDPE, compacted at 120°C, achieves the highest value at 2686.43 [N/mm2 ]. Conversely, the composition ratio of C5-5LLDPE, compacted at 135°C, yields the lowest modulus of elasticity at 1530.94 [N/mm2 ]. Elasticity modulus testing follows the ASTM D638 standard, with a speed of 2 mm/min. It is observed that increasing the compaction temperature results in a decreased modulus of elasticity across all composition ratios. Furthermore, a higher carbon content within the composite corresponds to a higher modulus of elasticity, regardless of the compaction temperature.